China's ancient principles of price regulation through market participation: The Guanzi from a comparative perspective - Isabella Weber (University of Massachusetts, Department of Economics, 2021)
The History of Economic Thought as a field has long taken it as a premise that so far as ancient economic thought is concerned, only the Greeks and Romans are worth studying. This paper introduces the Guanzi as a core text in ancient Chinese economic thought on price stabilization from a comparative perspective with ancient Greek contributions. The Guanzi presents a framework for the empirical analysis of market fluctuations and price movements and derives principles of economic governance from this analysis. In contrast Plato and Aristotle come to the question of price determination from the angle of moral philosophy. They foreground the right behaviour on the part of the individual not the structural features of the market. The Guanzi articulates the so-called "light-heavy" (轻重, qingzhong) principles, where heavy represents "important" or "essential" and light connotes "unimportant" or "inessential." It argues that essential subsistence goods and production inputs are always "heavy," while the relative importance of each commodity shifts with market fluctuations. It suggests that the markets are inherently unstable, if left to their own devises. The state should participate in the market of "heavy goods" in order to stabilize the economy as a whole.
Keywords: 330; History of Economic Thought; China; price theory; economic policy